Entrepreneurship among Faculty Members in the Jordanian Universities and its Relationship to their Strength: A Graduate Students’ Standpoint - Mahmoud Mohammed Daradkeh, Amjad; A.S. Tabieh, Ahmad; Y. Magableh, Atef (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to explore the relationship between the degree of availability of entrepreneurship among faculty members and its relationship to their strength from the standpoint of graduate students. Due to the nature of the study, the correlational descriptive approach is used. The questionnaire is used to collect data from the study sample of 270 male and female students, and their validity and reliability are also validated. The study shows that the degree of availability of entrepreneurship for a faculty member from the viewpoint of graduate students at the University of Jordan and the Middle East University ranks at a high level, and the strength of the faculty member is also high. It also shows that there is a positive correlation with statistical significance between the total degree of entrepreneurship and the degree of strength of the faculty member.